Overcoming challenges in implementing the WHO Surgical Safety Checklist: lessons learnt from using a checklist training course to facilitate rapid scale up in Madagascar. (29th September 2017) - Close, Kristin L; Baxter, Linden S; Ravelojaona, Vaonandianina A; Rakotoarison, Hasiniaina N; Bruno, Emily; Herbert, Alison; Andean, Vanessa; Callahan, James; Andriamanjato, Hery H; White, Michelle C
Abstract : The WHO Surgical Safety Checklist was launched in 2009, and appropriate use reduces mortality, surgical site infections and complications after surgery by up to 50%. Implementation across low-income and middle-income countries has been slow; published evidence is restricted to reports from a few single institutions, and significant challenges to successful implementation have been identified and presented. The Mercy Ships Medical Capacity Building team developed a multidisciplinary 3-day Surgical Safety Checklist training programme designed for rapid wide-scale implementation in all regional referral hospitals in Madagascar. Particular attention was given to addressing previously reported challenges to implementation. We taught 427 participants in 21 hospitals; at 3–4 months postcourse, we collected surveys from 183 participants in 20 hospitals and conducted one focus group per hospital. We used a concurrent embedded approach in this mixed-methods design to evaluate participants' experiences and behavioural change as a result of the training programme. Quantitative and qualitative data were analysed using descriptive statistics and inductive thematic analysis, respectively. This analysis paper describes our field experiences and aims to report participants' responses to the training course, identify further challenges to implementation and describe the lessons learnt. Recommendations are given for stakeholders seeking widespread rapid scale up of quality improvement initiatives to promote surgical safety worldwide.